The Direct Effects of a Corporate Income Tax - Bradley, Philip D. (Quarterly Journal of Economics, 1942)
Definition of direct tax effect, 638. — The theory of the firm, 639. — Diagrammatic presentation, 642. — The tax ratio, 644. — The tax ratio as a variable: a progressive tax, 646. — Comparison of tax effects and interest effects, 647. — The tax ratio as a constant: a proportional tax, 649. — Plans of more than two years' duration, 650. — Effects of the tax on other economic parameters, 652. — Implications for the theory of investment, 653. — Other implications, 654.